All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 208316 by Tawa11 last updated on 11/Jun/24
∫x2+3x2(x+1)(x2+1)2dx
Answered by Frix last updated on 11/Jun/24
∫x2+3x2(x+1)(x2+1)2dx==−3∫dxx+=−3ln∣x∣−+3∫dxx2+−3x++∫dxx+1++ln∣x+1∣++∫2xx2+1dx−+ln(x2+1)−−52∫dxx2+1+−52tan−1x−+12∫x2+2x−1(x2+1)2dx−x+12(x2+1)==−(7x2+x+6)2x(x2+1)+ln∣(x+1)(x2+1)x3∣−52tan−1x+C
Commented by Frix last updated on 11/Jun/24
12∫x2+2x−1(x2+1)2dx=t=tan−1x=∫(12+costsint−cos2t)dt==−22∫cos(2t+π4)dt=−24sin(2t+π4)==x2−2x−14(x2+1)=14−x+12(x2+1)=−x+12(x2+1)+C
Commented by Tawa11 last updated on 11/Jun/24
Thankssir.Ireallyappreciatesir.
Terms of Service
Privacy Policy
Contact: info@tinkutara.com